Paradocsis’ of clinical thinking (continuation of the discussion started in Tomsk by Osipov I.N., Kopnin P.V. in 50th of the 20th century) - V. P. Kaznacheev (Бюллетень сибирской медицины, 2003)
Considering the necessity to study the problems of propaedeutics of clinical medicine, besides the well-know syndromes by which the clinical diagnosis is formed, there are nosological syndromes of tiredness in which the changes of inner and outer environment are taken into account:1) non-liminal outer ecology,2) endoecological syndrom of tiredness,3) coagulopathy,4) syndrom of custom.Diagnostics of these syndromes makes it possible to form a new clinical diagnosis taking into account the changes of inner and outer environment which lead to genetic default and endoecology phenomenon.